Translating the Chinese Modal Particle 啊 (a) - Ko, Leong; Xu, Yang (International Journal of Linguistics, 2022)
The Chinese language has many modal particles, which often appear at the end of a sentence, hence also known as sentence-final particles. Such particles have specific functions and carry implied meanings in different contexts. However, modal particles are generally considered not existing in English, so their translation from Chinese into English presents a challenge for translators. This study focuses on the English translation of the Chinese modal particle 啊 (a) in sentence-final positions based on examples from three Chinese movies. The translated subtitles with the modal particle 啊 (a) are categorised into four types of sentences – namely, declarative, interrogative, exclamative and imperative. The examples are analysed within the framework of Nida’s functional equivalence theory by comparing the modal particle’s functions and meanings in the source and target texts. It was found that omission, explicitation and linguistic amplification are the three strategies used for rendering this modal particle, while omission is the dominant strategy. Though acceptable in many cases, omission may lead to the loss of functions or implied meanings. The findings suggest that translators should rely on an analysis of the context to decide which strategy is most appropriate to convey the function and implied meaning of 啊 (a).